2019
DOI: 10.4317/jced.56067
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution in fixed mandibular prostheses fabricated by CAD/CAM and conventional techniques: Photoelastic and strain gauge analyses

Abstract: BackgroundThe aim of this study was to evaluate the distribution of stress in complete fixed mandibular prostheses with infrastructures (IE) fabricated with different materials and techniques, under compressive force.Material and MethodsA model of an edentulous mandible, which received five 4x11 mm external hexagon implants between the mental foramens, was fabricated. The groups were divided into: Group I - IE in nickel-chromium with an acrylic resin occlusal coating; Group II – IE in nickel-chromium with a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In addition to that, all the maxillary prosthesis showed lower stresses in the bone surrounding the implant when opposed by a mandibular implant-supported acrylic prosthesis. These results correlate to the result obtained by other authors [ 18 , 28 , 29 ]. Another study showed that the use of acrylic resins resulted in a lower stress distribution when compared to ceramics [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to that, all the maxillary prosthesis showed lower stresses in the bone surrounding the implant when opposed by a mandibular implant-supported acrylic prosthesis. These results correlate to the result obtained by other authors [ 18 , 28 , 29 ]. Another study showed that the use of acrylic resins resulted in a lower stress distribution when compared to ceramics [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…When planning an implant-retained prosthesis, the clinical implication could change drastically depending on the surrounding conditions as intra-oral conditions are not always perfect. While some materials have been found to increase the amount of stress transmitted to the opposing prosthesis, other materials have been shown to transfer lower stresses [ 3 , 7 , 16 , 17 , 18 ]. As a result, it has been believed that the type of opposing structure influences the level of crestal bone change and the amount of stresses that are being transferred [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Bhering et al [ 50 ], rigid frameworks transmit lower load to the implant and prosthetic components, when compared to the less rigid ones. Nonetheless, variations of framework material rigidity did not demonstrate a significant effect on the stress values in the marginal bone around the implants [ 51 ] and Medeiros et al [ 26 ] observed that the occlusal coating had a greater influence on the load dissipations than the framework. In consonance with Erkmen et al [ 52 ] the current study demonstrated that by using less rigid material for milled bar in implant-retained prostheses the stresses within both, the framework and the veneering parts, decreased due to the flexible nature of the material that absorbs stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of biomechanical behavior can be performed through simulations to obtain pre-clinical data with bioengineering tools such as strain gauge, digital image correlation, photoelasticity and finite element analysis (FEA). The latter allows us to understand how the distribution of strain in bone tissue and stress in implants can be influenced by the restorative material [23], prosthesis and framework design [24,25], manufacturing technique [26], number and distribution of implants [27][28][29] and attachment systems [30,31]. Computer-assisted implant planning has become an important diagnostic and therapeutic tool in modern dentistry.…”
Section: Introductionmentioning
confidence: 99%